A DSC/TGA STUDY OF THE HETEROGENEOUS NUCLEATION OF CRYSTALLIZATION IN POLYPROPYLENE COPOLYMER - Nhan, Dang Duc; Quynh, Tran Min; Quy, Nguyen Hong (Vietnam Journal of Chemistry, 2014)
The study is aimed at the evaluation of the influence of nucleating agent (t-butyl)benzoic aluminum (NA) in changing clarity, crystallization temperature (Tp) and radiation resistant properties of polypropylene copolymer, PP (co) with 6% of ethylene. It has been shown that crystallization temperature of PP (co)+NA did not change when the content of the NA less than 2%, but the super cooling temperature is a little bit increased when the content of the NA was 2 or higher than 2%. Clarity of the blend comprising of PP (co)+NA decreases with the addition of 2% or more NA (t-butyl)benzoic aluminum. However, the increase of the supercooling temperature makes possible to improve radiation resistance of the material